ANALISIS PENANGANAN WABAH COVID-19 DALAM PERSPEKTIF MODEL COLLABORATIVE GOVERNANCE (STUDI KASUS PADA DESA KARANG REJO, KECAMATAN PURWOSARI , KABUPATEN PASURUAN) - Nur Chumairo; Aan Warul Ulum (Universitas Tribhuwana Tungga Dewi, 2021)
The Covid-19 pandemic, which has become a global disaster in the past one year and has not yet found a bright spot on when this pandemic will end, has resulted in unstable mobility of the country, one of which is in Indonesia. As a country with a high enough number of exposure, the government has issued an appeal or written regulation as an effort to prevent the spread of Covid-19. Various layers of society or the smallest sphere of government such as KarangRejo village have taken many actions in handling covid-19, by using the principle of collaborative governance, the government can run programs in the prevention or handling of covid-19 thoroughly because of the involvement of various sectors that work together to overcome the impact of the outbreak. covid-19. The method used in this research is qualitative descriptive by collecting primary and secondary data and through the process of observation and interviews so that it can be seen how programs and policies in handling the covid-19 outbreak in KarangRejo village when viewed from a collaborative governance perspective, which will be further discussed. in this collaborative governance perspective analysis journal of the handling of the covid-19 outbreak.Keywords: Collaborative Governance, Covid-19, GovermentPandemi covid-19 yang telah menjadi musibah global dalam jangka waktu satu tahun terakhir dan belum menemukan titik terang mengenai kapan pandemi ini berakhir, sehingga mengakibatkan mobilitas negara berjalan kurang stabil salah satunya di Indonesia. Sebagai negara dengan jumlah terpapar yang cukup tinggi mengakibatkan pemerintah mengeluarkan himbauan ataupun peraturan tertulis sebagai bentuk upaya pencegahan penyebaran covid-19. Berbagai lapisan masyarakat ataupun lingkup terkecil pemerintahan seperti desa Karang Rejo yang melakukan banyak tindakan dalam penanganan covid-19, dengan menggunakan prinsip collaborative governance pemerintah dapat menjalankan program dalam pencegahan ataupun penanganan covid-19 dengan menyeluruh karna terlibatnya berbagai sektor yang berkerjasama untuk menanggulangi dampak dari wabah covid-19. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan mengumpulkan data primer dan sekunder serta melalui proses observasi dan wawancara sehingga dapat diketahui bagaimana program dan kebijakan daalam penanganan wabah covid-19 di desa Karang Rejo jika dilihat dari perspektif collaborative governance , yang akan lebih jauh dibahas dalam jurnal analisa penanganan wabah covid-19 dalam perspektif collaborative governance ini.Kata Kunci : Collaborative Governance, Covid-19, Pemerintah